Validation of Lingual and Carcass Cyst with Enzyme Linked Immunoelectrotransfer Blot (EITB) for the Diagnosis of Porcine Cysticercosis - Joshi, Durga Datt; pandey, K. R.; Sekhar, R.; Dorny, P.; Bista, P. R.; Vercruysse, J. (Journal of Nepal Health Research Council, 2009)
Not uploaded. Key words: Cysticercosis; Porcine; Carcass; Lingual DOI: 10.3126/jnhrc.v6i1.2445 Journal of Nepal Health Research Council Vol. 6, No. 1, Issue 12, April, 2008 Page: 53-57